CRITICAL ISSUES IN MARRIAGE FAILURE IN BENIN CITY, NIGERIA: SIGNALING THE WAY FORWARD - Omage, Mannie I. (European Scientific Journal, ESJ, 2013)
Marriage is a sacred institution that must be well prepared for. Failure to plan before entering the union is planning to fail after entering the union. Every wedlock is bound either succeed of fail depending on the attitudes and inputs of the spouses involved. Marriage failure is a common feature in the Nigerian society and worldwide. Using Benin City, as the central focus, Copies of questionnaire were used to elicit data from a sample comprising 60 married respondents in the metropolis for the purpose of analysis and arriving at logical conclusions. From the research some factors associated with marriage failure are infidelity, witchcraft, unfriendliness, keeping secrets, poverty and in-laws’ intrusion, repeated quarrellings, unemployment, barrenness, spouse beating, religious ethnic differences and sickness. The manner in which partners in a union handle these critical issue signals matrimonial success or failure on the interim of eventually. The way forward cannot be detached from the role of the stakeholders; parents, in-laws, the government for a better counselling arrangement and most importantly the married partners themselves who must put up necessary adjustment to prevent marital failure and to cure matrimonial failure if it has already occurred in wedlock.